Tensile Properties of Polyhydroxyalkanoates/Calcium Phosphate through Simulation Analysis - Mazlan, Farah Yusra; Syed Abu Bakar, Sharifah Adzilla (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Tensile testing was done through simulation analysis by using Solidworks Simulation. Material used in this research is Polyhydroxyalkanoate (PHA) and Calcium Phosphate (CaP). The type of PHA used in this study is Polyhydroxybytyrate (PHB). Reinforced composites are popular for use in many industrial applications, because of their inherent high specific strength and stiffness. The aim of this study is to determine the the tensile properties of composite with different number of ply of PHA/CaP through simulation analysis and also to investigate the effects of different volume of samples based on ASTM standard on the tensile properties of composite. The ASTM standard is limited to ASTM D3039. ASTM D3039 specimens are rectangular in shape with a constant cross-section. The standard dimensions are length of 250mm, width of 25mm and thickness of 1 mm. Parameters that were used in this journal are the number of CaP ply in PHB composite and volume of composite CaP/PHB. The tensile properties of material have been identified through simulation testing through Solidwork software. The result shows that the higher number of CaP ply in PHB composite the lower the result of stress, displacement, and strain which will result in more strength. From the first set, 4/20 CaP ply in PHB composite has the lowest stress which was , displacement which was and strain which was . This proved that reinforcement of CaP help in enhance the physical properties of the final composite. The higher the volume of CaP/PHB composite the, lower the result of stress, displacement and strain which will result in more resistance of composite. From the second set, CaP/PHB volume of has the lowest stress which was , displacement which was and strain which was . This research prove that reinforcement CaP enhance the strength of final composite PHB.